Milk Lipid and Protein Profiles of Abkhazian and Kackar Goats - H. Iskender; O. Kaynar; A. Hayirli; Y. Camadan (Tropical Animal Science Journal, 2018)
Fat and protein profiles of milk of Abkhazian and Kackar goats, Caucasian breeds, were compared in this study. The milk samples (n= 60) from 60 Abkhazian and Kackar goats were subjected to assessments of lipid profile using the high performance thin layer chromatography and protein profile using the sodium dodecyl sulphate polyacrylamide gel electrophoresis. The milk lipid and protein contents as well as their fractions were compared using student t-test. Total lipid content was 4.23±0.022 g/dl and 3.44±0.026 g/dl for Abkhazian and Kackar goat milk (P<0.0001). Milk triacylglycerol, free fatty acid and diacylglycerol fractions were different (P<0.05), but the cholesterol fraction was similar. Total protein content was 3.94 g/dl and 3.75 g/dl for Abkhazian and Kackar goat milk (P<0.007). The milk fat globule membrane protein mucine1 and xhantine oxidase, α-lactalbumin, α-casein, and κ-casein fractions were different (P<0.05). In conclusion, milk lipid and protein profile differs between Abkhazian and Kackar goats despite living in the same ecosystem. Differences in milk lipid and protein profile could be pertinent to human nutrition and health.